2019
DOI: 10.4315/0362-028x.jfp-18-352
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Antimicrobial Profile of Bacterial Pathogens in Former Foodstuff Meat Products Used for Pet Diets

Abstract: European legislation stipulates that food no longer intended for human consumption, due to commercial reasons, manufacturing problems, or some defect, can be used in pet feed. However, the presence of former foodstuffs in pet diets could constitute a public health issue because pets can act as reservoirs of antimicrobial resistance genes. In this study, for the first time, biological hazards due to the presence of Escherichia coli and Salmonella in former foodstuff meat products were evaluated. Among the 112 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…In contrast, just one of 480 (0.2%) conventionally processed dog food samples yielded Salmonella in a study from the USA (Nemser et al ). A recent study in the Netherlands reported Salmonella isolation from 20% of 35 commercial raw food samples (van Bree et al ), while in Italy, pork and chicken material available for pet food manufacture yielded Salmonella from 12% of samples (Bacci et al ). Surveillance of Salmonella contamination in pet food by the APHA in the UK (under animal by‐products regulations) reported isolations from raw versus processed food in ratios of approximately 6:1 in 2015 and 20:1 in 2016, despite most samples coming from the larger processed food sector (APHA ).…”
Section: Risks Of Raw Feedingmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, just one of 480 (0.2%) conventionally processed dog food samples yielded Salmonella in a study from the USA (Nemser et al ). A recent study in the Netherlands reported Salmonella isolation from 20% of 35 commercial raw food samples (van Bree et al ), while in Italy, pork and chicken material available for pet food manufacture yielded Salmonella from 12% of samples (Bacci et al ). Surveillance of Salmonella contamination in pet food by the APHA in the UK (under animal by‐products regulations) reported isolations from raw versus processed food in ratios of approximately 6:1 in 2015 and 20:1 in 2016, despite most samples coming from the larger processed food sector (APHA ).…”
Section: Risks Of Raw Feedingmentioning
confidence: 99%
“…A higher prevalence of Salmonella in raw versus processed dog and cat foods was also reported in Egypt (Azza et al ). Serovars isolated in studies and surveillance of ingredients and raw food for pets or working dogs are diverse (Strohmeyer et al ) and include those considered to be of particular significance for human salmonellosis (Chengappa et al , Finley et al , Mehlenbacher et al , Bacci et al ). Indeed, in recent years in the UK, more than 50% of such regulated serovar isolations in animal feeding stuffs came from raw pet food, including tripe (APHA , ).…”
Section: Risks Of Raw Feedingmentioning
confidence: 99%
See 3 more Smart Citations